2019
DOI: 10.1159/000500556
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum Leptin Level Is Associated with Preoperative Pain Threshold and Postoperative Analgesic Consumption in Patients Undergoing Cesarean Section

Abstract: Objective: This study aimed to investigate the preoperative level of serum leptin in cesarean section (C-section) patients with and without acute labor pain and its association with postoperative analgesic consumption and preoperative pain threshold. Materials and Methods: Preoperative leptin levels, preoperative pain threshold, postoperative analgesic consumption in the first 24 h, and postoperative pain severity (visual analog scale (VAS) scores at 1, 2, 4, 6, 12, and 24 h postoperatively) in C-section patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“… 26 Recent studies have focused on the development of more objective predictors to evaluate pain after cesarean section. 27 , 28 On the one hand, postoperative pain affects maternal mental health, increases healing time, and reduces early mobility and functional activities, thereby increasing the length of hospital stay and leading to chronic postoperative pain. 29 , 30 However, it also prolongs the mother-infant relationship, affects breastfeeding, and affects the growth and development of newborns.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Recent studies have focused on the development of more objective predictors to evaluate pain after cesarean section. 27 , 28 On the one hand, postoperative pain affects maternal mental health, increases healing time, and reduces early mobility and functional activities, thereby increasing the length of hospital stay and leading to chronic postoperative pain. 29 , 30 However, it also prolongs the mother-infant relationship, affects breastfeeding, and affects the growth and development of newborns.…”
Section: Discussionmentioning
confidence: 99%
“…However, the method for determining if the patient would receive paravertebral blocks or local anesthesia infiltration preoperative is still controversial. Several studies proposed to predict the amount of postoperative analgesics in patients by measuring the sensitivity of preoperative patients to pain, anxiety, pain threshold, pain tolanrance threshold [18][19][20][21] . Thus, studies on the indication of paravertebral blocks and local infiltration anesthesia for PKP will be included in our future work.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of biomarkers prior to an operation may be useful in predicting analgesic consumption and improving postoperative pain management. 10…”
Section: Introductionmentioning
confidence: 99%
“…may be useful in predicting analgesic consumption and improving postoperative pain management. 10 Several studies have shown that preoperative levels of proteins or cytokines are associated with postoperative pain intensity or analgesic consumption, 10 and may potentially function as biomarkers to predict pain intensity. Proteins in the intracellular and extracellular matrix can act as biochemical alarmins for the immune system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation